Effect of zinc (Zn) supplementation on quality and quantity of striped catfish Pangasianodon hypophthalmus sperm - Kaliky, Nunun Ainun Putri Sari Banun; Setiawati, Mia; Carman, Odang; Utomo, Nur Bambang Priyo (Indonesian Society of Scientific Aquaculture (ISSA), 2019)
ABSTRACT This study aimed to evaluate the effects of Zinc (Zn) supplementation on the quality and quantity of striped catfish sperm. Experimental design for this study was a complete randomized design with five treatments and five replications. Male broods fed with Zn supplementation for eight weeks. The Zn supplemented into the fish diet at different concentrations (0, 50, 100, 150 and 200 mg/kg of feed). The results showed that Zn supplementation could improve the quality and quantity of striped catfish sperm. The treatments also showed significant effects on semen volume, sperm motility, sperm viability, and sperm concentration (P<0.05). Zn supplementation at a dose of 200 mg/kg feed demonstrated the best result has indicated by enhancement of quality and quantity of striped catfish sperm, increasing 51% of the volume, 11.6% of motility, 5.81% of viability, 54.1% of concentrations. The results suggested that Zn played an important role in improving reproductive performances of male striped catfish reproduction. Keywords: quality of sperm, a quantity of sperm, striped catfish, supplementation zinc ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh suplementasi Zinc (Zn) terhadap kualitas dan kuantitas sperma ikan patinPangasianodon hypophthalmus. Penelitian ini menggunakan rancangan acak lengkap dengan lima perlakuan danlima ulangan. Induk jantan diberi pakan dengan suplementasi Zn selama 8 minggu. Zn disuplementasikan dengan dosis berbeda (0, 50, 100, 150 dan 200 mg/kg pakan). Hasil penelitian menunjukkan bahwa suplementasi Zn dapat meningkatkan kualitas dan kuantitas sperma ikan patin sehingga berpengaruh signifikan terhadap volume semen, motilitas, viabilitas dan konsentrasi sperma (P<0,05). Suplementasi Zn pada dosis pakan 200 mg/kg menunjukkan hasil terbaik yang ditunjukkan oleh peningkatan kualitas dan kuantitas sperma ikan patin 51% volume; 11,6% motilitas; 5,81% viabilitas; 54,1% konsentrasi sperma. Hasil penelitian ini menunjukkan bahwa Zn memainkan peran penting dalam meningkatkan reproduksi ikan patin. Kata kunci: kualitas dan kuantitas sperma, Ikan patin, suplementasi Zn